PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU SMP BERPRESTASI DENGAN METODE AHP DAN PROMETHEE (STUDI KASUS: SEKOLAH NEGERI KOTA PONTIANAK) - Manalu, Sulimargos (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
In order to improve the quality of teachers and education personnel and reward to the professionalism of teachers and lecturers then organized activities aimed at motivating teachers to improve their competence, one of which is make an elections competition outstanding teachers that represent each school where the teacher is teaching. In this outstanding teacher assessment process required criteria and sub-criteria that have been determined by Pontianak City Department of Education. The criteria and sub-criteria used in the selection of outstanding teachers refer to the technical manual selection of teachers, principals and school superintendents and chief achievement and special education teachers / pk dedicated in 2014. Decision Support System designed by combining AHP and Promethee to help those who are entitled to give a decision for each participant selection of teachers. In the decision support system designed performed two types of testing, which is the first to compare the combination of AHP and Promethee, AHP itself, Promethee itself and the second some user feedback through User Acceptance Test (UAT). From the results of the comparison method, the AHP, Promethee, and AHP-Promethee method the result is approached from the manual assessment is AHP-Promethee (method contained in the Decision Support System). Based User Acceptance Test, it can be concluded that the Decision Support System designed assessed successfully demonstrated with an average value of 85.316% for the administrator level, 86.278% to the level of the jury, and 85.743% for the level of participants.Â